2020
DOI: 10.1097/inf.0000000000002671
|View full text |Cite
|
Sign up to set email alerts
|

Isavuconazole As Successful Salvage Therapy for Mucormycosis in Pediatric Patients

Abstract: Background: Mucormycosis is a rare but emerging life-threatening fungal disease with limited treatment options. Isavuconazole is a new triazole that has shown efficacy in adults for primary and salvage treatment of mucormycosis. However, data in children are scarce. Methods: The demographic and clinical data of pediatric patients with proven mucormycosis who were treated with isavuconazole in 2015 to 2019 at 2 centers were collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…Our results align with previous reports, where patients received ISA as a salvage therapy for a proven IFI and showed a complete regression of the infection, with few adverse events and similar ISA exposure levels within the recommended range of 2–4 mg/L, as shown in Table 2 [ 6 , 7 , 8 , 10 , 11 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results align with previous reports, where patients received ISA as a salvage therapy for a proven IFI and showed a complete regression of the infection, with few adverse events and similar ISA exposure levels within the recommended range of 2–4 mg/L, as shown in Table 2 [ 6 , 7 , 8 , 10 , 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, its use is off-label in the pediatric population, and optimal dosing and monitoring remain unclear. Articles and case reports suggest the administration of adult dosing in children over 30 kg, and half the dosing for children under 30 kg [ 6 , 7 , 8 , 9 ]. In those reports, tolerance, safety, and therapeutic response were evaluated, mostly in adolescent patients [ 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…All other limited available evidence of isavuconazole in the pediatric setting refers to the treatment of invasive aspergillosis or mucormycosis as salvage therapy after clinical failure with first-line therapies. 18,19,[34][35][36][37][38][39][40][41][42] Overall, this comparative study confirms that even in a pediatric setting, an approach based on real-time CPAs performed by MD clinical pharmacologists and based on TDM results should be considered mandatory when using voriconazole, whereas the same approach should not be necessary in most cases involving isavuconazole. Notably, the implementation of a similar real-time CPA program should be carefully considered in centers managing pediatric patients with hemato-oncological malignancies requiring high-intensity treatment to personalize and maximize antifungal prophylaxis or treatment.…”
Section: Discussionsupporting
confidence: 66%
“…Isavuconazole can be administered as prophylactic treatment for susceptible cases but can lead to breakthrough fungal infections just like the case with voriconazole and posaconazole [164]. Isavuconazole has also been used as salvage therapy for treating invasive mucormycosis in pediatric patients and satisfactory results have been demonstrated in the case series by Ashkenazi-Hoffnung et al [167]. Marty et al reported a mortality of 33% in their series when they treated mucormycosis with isavuconazole versus 39% for amphotericin B with the conclusion that the efficacy of isavuconazole is similar to amphotericin B for invasive mucormycotic infections [168].…”
Section: Spectrum Of Activitymentioning
confidence: 99%